Analisa Kapasitas Struktur Intake Rumah Pompa Karang Anyar, Pulokerto - Anthony Costa; Ahmad Yudi (Civil Infrastructure Engineering and Architectural Design, 2021)
Intake Building Structure is a Pier Type Structure that is used as a building for the distribution of clean water. This structure stands on a stake that stands on the edge of the river, as a pier-type building that accepts the load of river currents and pump vibration loads, it is necessary to analyze the maximum capacity, economical and also sturdy. There are several important aspects that must be reviewed to get the maximum design, including water current load, soil load, pump vibration load and also earthquake load in the form of spketrum response based on Palembang area. The design reference used is SNI1727-2013 and SNI 1726-2002. Based on the analysis, the intake structure was obtained in the form of reinforced concrete structures on the floor area and pilecap while for the foundation of the stake in the form of composite steel, columns and beams because it supports a heavy enough load, the profile steel is used.